Judging the Neonatal Abstinence Syndrome Assessment Tools to Guide Future Tool Development: The use of Clinimetrics as Opposed to Psychometrics - Westgate, Philip M.; Gomez-Pomar, Enrique (Frontiers in Pediatrics, 2017)
In the face of the current Neonatal Abstinence Syndrome (NAS) epidemic, there is considerable variability in the assessment and management of infants with NAS. In this manuscript, we particularly focus on NAS assessment, with special attention given to the popular Finnegan Neonatal Abstinence Score (FNAS). A major instigator of the problem of variable practices is that multiple modified versions of the FNAS exist and continue to be proposed, including shortened versions. Furthermore, the validity of such assessment tools has been questioned, and as a result the need for better tools has been suggested. The ultimate purpose of this manuscript therefore is to increase researchers’ and clinicians’ understanding on how to judge the usefulness of NAS assessment tools in order to guide future tool development and to reduce variable practices. In short, we suggest that judgment of NAS assessment tools should be made on a clinimetrics viewpoint as opposed to psychometrically. We provide examples, address multiple issues that must be considered, and discuss future tool development. Furthermore, we urge researchers and clinicians to come together, utilizing their knowledge and experience, to assess the utility and practicality of existing assessment tools and to determine if one or more new or modified tools are needed with the goal of increased agreement on the assessment of NAS in practice.